Light - science and magic : an introduction to photographic lighting. - Hunter, Fil, ....-; Biver, Steve, ....-; Fuqua, Paul, ....- (Amsterdam : Elsevier, 2012)
This is better than all the other how to books on the market which just provide set examples for photographers to follow. Light Science and Magic provides photographers with a comprehensive theory of the nature and principles of light to allow individual photographers to use lighting to express their own creativity. It will show you in-depth how to light the most difficult subjects such as surfaces, metal, glass, liquids, extremes (black-on-black and white-on-white), and people. With more information specific for degital photographers, a brand new chapter on equipment, much more information on location lighting, and more on photographing people, you'll see why this is one of the only recommended books by www.strobist.com.
Keywords: Elektronica; Fotografie